InSAR monitoring of dam deformations in a seismically active region of Kazakhstan for identifying precursors of failure - Talgarbayeva, Dinara; Vilyaev, Andrey; Dedova, Tatyana; Kuznetsova, Oxana; Jangulova, Gulnar (Frontiers in Earth Science, 2025)
Assessing the condition of hydraulic structures (HS) is critical to minimizing the risks to the population and infrastructure in the event of their collapse. HS in seismically active regions are particularly hazardous, as natural and man-made factors can combine to cause catastrophic consequences. This paper analyzes the causes of the Voroshilov Reservoir dam breach (Kazakhstan, a seismically active region, March 2024) using Satellite Radar Interferometry (InSAR) and Ground Penetrating Radar (GPR) profiling. InSAR revealed a persistent upward trend in dam deformations (amplitude over 30 mm since spring 2022), presumably associated with swelling of waterlogged soil. GPR data obtained 2 months after the reservoir was drained confirmed abnormally high moisture content throughout the dam, indicating chronic filtration and the development of internal erosion. A moderate correlation was found between deformations and microseismic activity in the region. It was concluded that the combination of high filtration, soil instability, microseismicity and structure wear led to the accident. Our research shows that a wavy pattern of displacements with a sharp increase in amplitude in earthen dams is a key indicator of critical moisture saturation, forewarning a breach or failure. Furthermore, unstable deformation dynamics during seismic events are also a crucial sign for monitoring dams in earthquake-prone areas.